ALS/SURV: a modification of the CAFS statistic. Issue 7 (2nd October 2019) - Goutman, Stephen A.; Brown, Morton B.; Cudkowicz, Merit; Atassi, Nazem; Feldman, Eva L.
Abstract: We present a composite endpoint that can be used in amyotrophic lateral sclerosis (ALS) trials, which combines functional status (via the ALS functional rating scale) and survival, denoted ALS/SURV. ALS/SURV modifies and extends the combined assessment of function and survival (CAFS) score and assigns rankings to participants that withdraw or are lost to follow up in a way that does not disproportionately lower and skew ranks for those participants that reach study endpoint (either death or study completion). ALS/SURV has properties of: (1) ordering participants that completed the study from the shortest surviving participant to the last observed death followed by worst function to best function; (2) ordering participants withdrawing at time of withdrawal by their decline in functional status relative to all the participants still in the study; and (3) then maintaining this ordering at time of withdrawal relative to participants still in the study. These properties allow ALS/SURV to better account for participant drop out compared to CAFS. We derive and compare the rankings of participants from the ceftriaxone treatment trial for ALS/SURV and CAFS and demonstrate that ALS/SURV does not modify the ordering of participants that complete a study by the results of participants who withdraw. Additionally, ALS/SURV can be summarized as either median functional status or median survival along with interquartile range, thereby adding clinical meaning to the statistic. Finally, by applying normal deviates, confidence intervals can be computed and used to estimate power for future studies. In summary, the above properties support the role for ALS/SURV as a new ALS composite statistic.